CP-156 Prescribing pattern, tolerability and efficacy study (4 weeks) of the novel drug 'xiapex'. (14th February 2016) - Fantini, L; Iovino, P; Polidori, C; Boriani, F; Cioni, S; Trombetta, L; Sassoli, V
Abstract : Background: Xiapex (active ingredient: collagenase Clostridium histolyticum ), is a novel, innovative and expensive drug under observation from the Italian Medicine Agency (AIFA). Its dispensation is authorised only in highly specialised hospitals, such as this hospital, where it has been given to patients with Dupuytren disease since 4 December 2014. By law the drug is allowed to be given 3 times on the same palmar fascia for 4 weeks. Purpose: To monitor Xiapex utilisation pattern (drug prescribing pattern, tolerability and efficacy study) over a 10 month period of marketing. Material and methods: From the AIFA database the eligibility criteria for Xiapex treatment were obtained: the joint involved in the treatment (metacarpophalangeal (MP) or proximal interphalageal (PIP)); degree of contracture (between 20 and 50 for MP; between 15 and 40 for PIP); prior surgical intervention (only aponeurotomy or fasciotomy); and other concomitant disease (diabetes, hypercholesterolaemia, tabagism, alcoholism, epilepsy cirrhosis or HIV). Personal and clinical data of all 24 patients (pz) were available from the doctor records as well as data on tolerability and efficacy of the drug after 4 weeks of treatment. Results: Patient age ranged from 40 to 90 years. 4 were women and 20 were men. 5 pz presented other disease: 2 diabetes, 2 hypercholesterolaemia, 1 tabagism. 22 pz had MP contracture as the main issue. In particular, 11 pz had a contracture score of 30, 2 pz a score of 35, 7 pz a score of 40 and 2 pz a score of 50. 2 pz were affected by the PIP contracture as the main issue. In particular, 1 pz had a score of 35 and the other a score of 40. Only 2 pz had previous fasciotomy. All 24 pz were treated once and this treatment was sufficient to resolve the Dupuytren's contracture (specifically the remaining residual delta of muscolar contraction was trascurable). Only minor, modest and short side effects were observed, such as skin rush at the armpit, light skin abrasions and ecchymosis. Conclusion: These preliminary results show that clinically different patients, but within the AIFA criteria, benefit from the treatment with very few side effects in all patients. No conflict of interest.